2017
DOI: 10.1002/adma.201605175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of the Nature of Weak Chemical Bonds in Labile Compounds

Abstract: and crystallize them. Fortunately, developments in synthetic strategies, especially for a concept of kinetic protection by bulky substituents, [1] have enabled us to sufficiently stabilize transient species with weak chemical bonds, in order to produce single crystals for X-ray diffraction studies. Using such molecules, the nature of the chemical bonds and orbital distributions have been characterized based on experimentally obtained EDDs, focusing on valence electrons as well as the crystal and molecular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A consideration of the reaction sequence of the formal (3 + 2) cycloaddition, comprising addition and cyclization, led to two queries: (1) whether our bifunctional activation mechanism , can be applied to synthesize other diastereomers of the (3 + 2) adduct and (2) if the enantio- and diastereoselectivity in the reaction with two isomerizable substrates can be explained by the Curtin–Hammett principle . The aforementioned model was supported by various spectroscopic analyses of the Ni­(II) complex in the ground state, on the basis of the electron density distribution (EDD) analysis of the Ni­(II)-diamine-acetate complex (CCDC 1482741) . However, a computational validation of the TSs has not been systematically conducted.…”
Section: Introductionmentioning
confidence: 97%
“…A consideration of the reaction sequence of the formal (3 + 2) cycloaddition, comprising addition and cyclization, led to two queries: (1) whether our bifunctional activation mechanism , can be applied to synthesize other diastereomers of the (3 + 2) adduct and (2) if the enantio- and diastereoselectivity in the reaction with two isomerizable substrates can be explained by the Curtin–Hammett principle . The aforementioned model was supported by various spectroscopic analyses of the Ni­(II) complex in the ground state, on the basis of the electron density distribution (EDD) analysis of the Ni­(II)-diamine-acetate complex (CCDC 1482741) . However, a computational validation of the TSs has not been systematically conducted.…”
Section: Introductionmentioning
confidence: 97%
“…X-ray crystal structure analysis revealed that the two fluorenyl rings in 1 perpendicularly face each other (the bond angle θ C2−C1−C3 = 89. 19(3)°), instead of having a propeller-like structure (Figure 2b), and a distant C−C interatomic contact was found between the carbon atoms (C2 and C3 in Figure 2b) at the 9-positions of the facing fluorenyl rings. On the basis of single-crystal X-ray analysis, the C−C distance was determined to be 2.0415(5) Å at 90 K, and this distance was well-reproduced (2.0478 Å) by the density functional theory (DFT) calculation at the B3LYP-D3/6-311+G** level of theory (see Table S1 for a DFT benchmark study).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To gain deeper insight into the electronic interaction between C2 and C3, we performed electron density distribution (EDD) analysis to visualize the distribution of valence electrons in the crystalline state. 19 The single-crystal X-ray diffraction data of 1 were obtained up to [sin θ/λ] max = 1.11 Å −1 using Mo Kα radiation at 90 K. Figure 2c,d shows the static model deformation density maps 20,21 of 1 (90 K) on the C1−C2−C3 plane and the cross section of the C1−C2−C3 plane through the skeletal carbons, respectively. A concentration of electron density (peak height ≈ +0.03 e Å −3 , green circle in Figure 2c,d) is apparently recognized between C2 and C3, indicating orbital overlap that allows the sharing of electrons in the C2−C3 region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Considering that the parent fluorenyl radical possesses a large spin density of >0.5 at the 9position 17 , an appreciable electron-electron interaction appears to be present between C2 and C3. To gain deeper insight into the electronic interaction between C2 and C3, we performed electron density distribution (EDD) analysis to visualise the distribution of valence electrons in the crystalline state 18 . The single-crystal X-ray diffraction data of 1 were obtained up to [sinθ / λ]max = 1.11 Å −1 using Mo Kα radiation at 90 K. Figures 1c and 1d show the static model deformation density maps 19,20 which was estimated from the singlet-triplet vertical excitation energy (ΔES-T) by a B3LYP-D3/6-311+G** calculation of 1 (90 K), reached up to 138 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%